2021
DOI: 10.1186/s13643-021-01760-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic side effects of antipsychotic drugs in individuals with schizophrenia during medium- to long-term treatment: protocol for a systematic review and network meta-analysis of randomized controlled trials

Abstract: Background Antipsychotic drugs and especially the newer compounds are known to cause metabolic side effects. However, a comprehensive comparison of the different substances regarding their propensity to cause metabolic side effects in medium- to long-term treatment of schizophrenia is lacking. Methods We will conduct a systematic review and network meta-analysis (NMA). We will include randomized controlled trials (RCTs) in which participants receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We report following the Preferred Reporting Items for System­atic Reviews and Meta‐Analyses (PRISMA) extension statement for network meta‐analyses. The study protocol was registered with PROSPERO (registration number: CRD42020175414) and published 17 .…”
Section: Methodsmentioning
confidence: 99%
“…We report following the Preferred Reporting Items for System­atic Reviews and Meta‐Analyses (PRISMA) extension statement for network meta‐analyses. The study protocol was registered with PROSPERO (registration number: CRD42020175414) and published 17 .…”
Section: Methodsmentioning
confidence: 99%
“…To date, no comprehensive comparative studies have addressed whether and how antipsychotic-induced metabolic side effects differ between medium- and long-term therapy. Most recently, Schneider-Thoma et al [ 28 ] reported a protocol for conducting a meta-analysis of randomized controlled trials of antipsychotic drug-associated metabolic side effects (primarily weight gain and disturbances of glucose and lipid metabolism) in schizophrenia patients during medium- to long-term treatment. Their systematic review is presumably ongoing; no results have been reported to date.…”
Section: Side Effects Of Antipsychotic Drugsmentioning
confidence: 99%
“…In the first place, despite 70 percent or more receptor occupancy, standard antipsychotics are not helpful for all Oxidative Medicine and Cellular Longevity people with schizophrenia [3]. Second, traditional antipsychotics are only successful in treating about 70% of positive symptoms [4] and have been reported ineffective in treating negative and cognitive symptoms [95].…”
Section: Impacts Of Antipsychotic Medicationsmentioning
confidence: 99%